Tribulus terrestris extract protects against mercury-induced - S. Sankar Samipillai, T.Sugunavarman, G. Jagadeesan (Journal of Ecobiotechnology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Mercury is a highly toxic metal which induces oxidative stress in the body. In this study we aimed to investigate the possible protective effect of Tribulus terrestris, an antioxidant agent, against experimental mercury toxicity in rat model. Following a single dose of 2 mg/kg mercuric chloride (HgCl2; Hg group) either saline or Tribulus terrestris (50 mg/kg) was administered for 15 days. After decapitation of the rats trunk blood was obtained and the tissue samples from the liver and kidney were taken for the determination of Lipid peroxidation and glutathione (GSH) levels. AST, ALT, BUN andÃ‚Â Creatinine levels were assayed in serum samples. The results revealed that HgCl2 induced oxidative damage caused significant decrease in GSH level, significant increase in LPO activity content of the tissues. Treatment of rats with Tribulus terrestris significantly increased the GSH level and decreased the LPO. Similarly, serum ALT, AST and BUN and Creatinine levels were elevated in the mercuryÃ‚Â group as compared to control group. On the other hand, Tribulus terrestris treatment reversed all these biochemical indices. Our results implicate that mercury-induced oxidative damage in liver, and kidney tissues protected by Tribulus terrestris extract, with its antioxidant effects.